Wilforlide A ameliorates the progression of rheumatoid arthritis by inhibiting M1 macrophage polarization - Yunxiang Cao; Jian Liu; Chuanbing Huang; Yanhong Tao; Yuan Wang; Xi Chen; Dan Huang (Elsevier, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease with increased M1 macrophages. The classical activated M1 macrophages produce various cytokines to control inflammation. Wilforlide A is a natural product that displays anti-inflammatory activities. However, the effect of Wilforlide A on RA progression and the potential mechanisms are unclear. Herein, the collagen-induced arthritis (CIA) mouse was used as an experimental model of RA. The administration of Wilforlide A reduced clinical scores, joint swelling and histological damage in ankle joints of RA mice. The secreted pro-inflammatory factors (MCP1, GM-CSF and M-CSF) and M1 biomarker iNOS in synovium were inhibited by Wilforlide A. In vitro, macrophages deriving from THP-1 cells were stimulated with LPS/IFN-γ to mimic M1 polarization. Similarly, Wilforlide A blocked macrophages polarizing towards M1 subsets. The in vitro results demonstrated that Wilforlide A suppressed LPS/IFN-γ-induced TLR4 upregulation, IκBα degradation and NF-κB p65 activation. In addition, TAK242 (a TLR4 inhibitor) treatment caused a similar inhibitory effect on M1 polarization with Wilforlide A, whereas it was less than the combination of TAK242 and Wilforlide A. Therefore, this work supports that Wilforlide A ameliorates M1 macrophage polarization in RA, which is partially mediated by TLR4/NF-κB signaling pathway inactivation.